Multi-year consumption analysis and innovative energy perspectives: The case study of Leonardo da Vinci International Airport of Rome. (15th November 2016) - de Rubeis, Tullio; Nardi, Iole; Paoletti, Domenica; Di Leonardo, Antonella; Ambrosini, Dario; Poli, Ruggero; Sfarra, Stefano
Highlights: A systematic approach for energy management of complex structures is proposed. Technological systems of Leonardo da Vinci Airport of Rome are described. A multi-year consumption analysis highlights the most energy-consuming sectors. The "Smart Grid" prototype project inherent to T1 Terminal is presented. Wind and photovoltaic plants are designed and discussed to test the smart storage. Abstract: Because of the growing need for efficient energy production systems, energy policies promoted in recent years have also involved complex structures, like airports. This paper proposes the implementation of an energy management system for a very energy-consuming structure, composed of different power plants and many energy consumers: the Leonardo da Vinci International Airport of Rome. In this study, the examination of historical data related to airport electric power, thermal energy and fuel consumption is discussed, starting with the analysis of the production energy plants, mainly based on a combined heat and power system. Furthermore, pioneering solutions are proposed, not only to cover airport energy requirements, but also to test the safety and reliability of innovative load management systems. For this reason, the choice of the Leonardo da Vinci management company, oriented to install a smart storage in order to manage the bidirectional energy flows by consumers and producers, is justified. Such innovative energy procurement systems are examined, with the goal of achieving greater penetration of renewable sources: mini and micro wind power plants and high concentrator photovoltaic plants.